Synthesis of Graphite Porous Electrode Based on Coconut Shell as a Potential Cathode in Bioelectrosyntesis Cell - Aris Mukimin; Rustiana Yuliasni; Nur Zen; Kukuh Wicaksono; Januar Arif Fatkhurahman; Hanny Vistanty; Rizal Awaludin Malik (Universitas Gadjah Mada, 2019)
Electrodes, as well as microorganisms, are key materials for the development of bioelectrosynthesis cell reactor. Materials used as electrodes should be inert, crystalline in structure with high surface area and porous morphology, enhancing their electroactive and adsorptive properties. Carbon material derived from coconut shell was modified by simultaneous sintering-activation methods, FeCl3 and ZnCl2 were supplemented at temperature 900 °C at the non-atmospheric condition. The modified carbon was then molded with polyvinyl alcohol as a binder and the temperature was maintained at 80 °C and 10 ton of pressure. Molded carbon was then installed in bioelectrosynthesis cell with a working volume of 200 mL, as a cathode. XRD, BET, and SEM measurements showed the transformation of carbon surface from amorphous into the crystalline, increased surface area (11 times higher) and higher porosity (up to 500 nm). This cathode modification was able to increase current density up to 4 times and reduce CO2 into butyrate, 250 mg/L, in bioelectrosynthesis cell.